A simplified technique to fabricate complete dentures from the previous prosthesis duplication for elderly patients (Research, Society and Development, 2020)
Introduction: The time required for the complete dentures confection may be a limiting factor in the treatment of geriatric patients since these patients have age-related systemic conditions and morbidities that limit their mobility. Also, the elderly ability to adapt to a new prosthesis with very different characteristics from the existing ones can be difficult. Methodology: This present study aims to describe a simplified technique to fabricate the complete dentures in two visits by duplicating the patient existent prosthesis, with the teeth area confectioned in wax and the other parts made of acrylic resin. The technique consists of using the replica of the patient's existent prosthesis to record the maxillomandibular relations and as a vehicle for obtaining the functional cast. Results: This technique showed the improvement of the esthetic factors, an increase of the occlusal vertical dimension, and lip support when compared to the patient’s previous prosthesis. Conclusion: This technique allows the reduction of clinical steps and provides the patients with an easier adaptation of the new prosthesis.